La radio et la télévison au Maroc - Ahmed Hidass (Communication)
The high degree of illiteracy in combination with the limited readership of the written press, make radio and television the premiere media in Morocco. In order to safeguard its image and diffused its message, the Maghzen (the State) have made radio and television subject to its guardianship. For reasons of prestige, and conjuncture, the State initiated the creation of a private television and a private radio broadcaster. Under pressure, the governing bodies of these broadcasters have been ones of alternation. Is this a sign of democratization ? If so, freedom of opinion and expression would come out winners ! In order to answer this question, the RTM, the public radio and television station dictates choice. It bears no witness to change. The sovereign media of the State, its structure and editorial policy makes allies of official priorities, fixed language and blackouts.